Guy Wolff : master potter in the garden - Staubach, Suzanne (University Press of New England, 2013)
If you mention Guy Wolff to a serious gardener, that gardener will almost certainly admit to either owning a Guy Wolff flowerpot or coveting one. Wolff's pots - some small and perfect for a sunny windowsill, others massive and just right for a favorite outdoor spot - are widely considered to be the epitome of gardenware. Their classical proportions, simple decoration, and the marks of Wolff's hands all combine to make plants look their best. His pots possess an honesty and liveliness that machine-made flowerpots lack, and Wolff is among the best-known potters working in the United States in the early twenty-first century. This book explores Wolff's works.